Posture stability control of a small inverted pendulum robot in trajectory tracking using a control moment gyro. (2nd May 2020) - Tanaka, Kunitoshi; Nagasawa, Sumito
ABSTRACT: This paper reports on a posture stability control method for an inverted pendulum robot using a control moment gyro (CMG) mounted on the top of the inverted pendulum. As an inverted pendulum dimension decreases, a time to fall over to an angle where an inverted pendulum cannot restore its posture becomes shorter; however, a small inverted pendulum robot cannot have a powerful computer because of space limitations. This means it requires a faster and smaller way to maintain its balance. Furthermore, inverted pendulum robots require movement space to gain a restoring force to keep their balance. We thus proposed an inverted pendulum robot using a CMG to obtain the necessary restoring force. The CMG's effects decreased the robot's falling over speed, meaning it can keep its balance without moving. We successfully demonstrated that an inverted pendulum robot with a CMG can separate posture stability control and trajectory tracking control. The validity of the inverted pendulum robot with a CMG was confirmed comparing the two experiments. In the first experiment, the CMG performed posture stabilization and the wheel performed trajectory tracking. In the second experiment, only the wheel performed posture stabilization and trajectory tracking. GRAPHICAL ABSTRACT: